Progreso en el CIAT Palmira, Colombia en mejoramiento de resistencia a Xanthomonas campestris phaseoli (X. phaseoli) en frijol para la zona tropical - Beebe, Stephen E. (International Center for Tropical Agriculture, 1982)
Crosses were made and cv. and lines selected to combine the existing resistance to Xanthomonas campestris pv. phaseoli with adaptation to the tropics and to determine new sources of resistance. Crosses were made between adapted lines and sources of resistance, some with Great Northern genes. The greenhouse inoculation method was modified for field use thus allowing large F2 populations to be inoculated and seed setting, plant architecture, and agronomic value of these selections to be monitored. After 2 yr there are lines with intermediate to resistance reactions, better adapted to CIAT conditions and with a broad color range, including red brilliant and black opaque. In Sept. 1981 some of these lines were planted in Guatemala, El Salvador, Honduras, Nicaragua, Costa Rica and several showed a better adaptation to Central American conditions than to those at CIAT. Other possible sources of resistance were evaluated as parent materials but most of them did not combine well in crosses. Some sources were eliminated on the basis of their performance in crosses. Other sources with progenies as advanced breeding lines are G04826, G05147, G04399, and ICA Linea 23. (AS)